Enhancing protein extraction from soybean expeller: Exploring the impact of precipitating agents and flour-to-water ratios on functional properties - Andrín, María Nieves; Guraya, María Angeles; Accoroni, Cecilia; Torresi, Pablo Antonio; Godoy, Ezequiel; Reinheimer, María Agustina (Akadémiai Kiadó, Budapest, 2024)
This study investigates sustainable methods for producing protein from soybean expeller via pH-shifting processes, aiming to reduce water usage in alkaline extraction by adjusting solid-to-liquid ratios per cycle and employing isoelectric precipitants like lactic acid and lactic acid bacteria (Lactiplantibacillus plantarum and Lactococcus Lactis) to enhance functional and antioxidant properties over a wide pH range. Results indicate that the most efficient approach involves three 1:10 (w/v) extraction cycles with lactic acid bacteria as precipitants, demonstrating high productivity and low specific water consumption. Protein content and recovery yield showed no significant differences compared to alternatives with higher water consumption or less eco-friendly precipitants. Despite lower solubility, protein products precipitated with lactic acid bacteria formed stable emulsions, exhibiting superior free radical scavenging activity.